Perancangan Marketing Gallery & Club House dengan Pendalaman Prinsip Health and Wellbeing - Hamidah, Otovianisa Dipa; Wardhani, Dyah Kusuma (Aksen : Journal of Design and Creative Industry, 2022)
Humans will essentially live influenced by the environment. Human life continues to thrive in line with lifestyle and the natural environment. in line with the development of the era from time to time, several new problems arise due to changes in lifestyle and the natural environment. Humans who are increasingly facilitated by technology in doing everything, spend a lot of time indoors. This gives rise to new phenomena that are not considered a serious problem by space users. It will have a more negative impact if allowed to occur continuouslyNot only operational and aesthetic functions are considered in the design of a space in a building, but all things that affect the physical health and well-being of users, as well as connectivity with nature, should also be considered. Marketing Gallery & Clubhouse is a facility and infrastructure owned by property developers to meet the company’s operational support facilities as well as to complement public facilities for the local people. The focus issue is how to apply the principles of health & wellbeing as a solution to improve the quality of life of users, while also facilitating all the needs and convenience of users in it. Interior design with the application of health & wellbeing principles is applied to the design process of the Marketing Gallery & Clubhouse Citraland Puncak Tidar in Malang. The method used in market research is literature study and analysis. While the methods used in the design are problem identification, problem exploration, problem redefinition, and solution proposal.